2013 IEEE 15th International Conference on E-Health Networking, Applications and Services (Healthcom 2013) 2013
DOI: 10.1109/healthcom.2013.6720631
|View full text |Cite
|
Sign up to set email alerts
|

mHealth for cardiac patients telemonitoring and integrated care

Abstract: In the majority of developing economies there has been limitation to rapid growth of technologyrich and expensive broadband telecommunication infrastructure (e.g. optical fiber networks), which is prerequisite of e-Health. However, along with the emergence of broadband mobile communication networks, mHealth seems advantageous and costefficient mode of e-Health in those countries, likewise Georgia. The first mHealth project in Georgia on m-Telemonitoring (MTM-1) of Cardiac arrhythmia -54 patients with main medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The Chapidze Emergency Cardiology Centre in Georgia is pioneering the use of mHealth to monitor cardiac arrhythmias (irregular heartbeats) and hypertension (high blood pressure) in patients. A study carried out by the Centre and Tbilisi State Medical University into mHealth for cardiac patient telemonitoring and integrated care found that when mHealth was used to monitor cardiac arrhythmias it shortened hospital stays and had a positive impact on quality of life, because patients were able to go home sooner (110).…”
Section: Electronic Patient Informationmentioning
confidence: 99%
“…The Chapidze Emergency Cardiology Centre in Georgia is pioneering the use of mHealth to monitor cardiac arrhythmias (irregular heartbeats) and hypertension (high blood pressure) in patients. A study carried out by the Centre and Tbilisi State Medical University into mHealth for cardiac patient telemonitoring and integrated care found that when mHealth was used to monitor cardiac arrhythmias it shortened hospital stays and had a positive impact on quality of life, because patients were able to go home sooner (110).…”
Section: Electronic Patient Informationmentioning
confidence: 99%
“…In this series, Chen et al [4] presented patient monitoring use case of mHealth to highlight the new needs in terms of data access control, location awareness, prioritization and mobility levels while developing the mHealth solution. Kirtava et al [6] presented mHealth solution for cardiac patients. They reported feasible methodology to monitor cardiac arrhythmia in outpatients in Georgia, promoting earlier discharge of nonlifethreatening cases, improving patients' comfort of life and increasing their mobility with enhanced safety.…”
Section: IImentioning
confidence: 99%
“…Several studies have demonstrated the positive impacts of mHealth projects towards developing nations. These benefits include, widening access to healthcare services particularly for remote communities, lowering service costs for financially challenged or resource scarce areas, promoting the dissemination of health education thereby improving disease monitoring and treatment, as well as supporting health providers by providing efficient portable tools (26,27). Telecommunication technologies, especially mobile phones have contributed greatly to the successful implementation of mHealth initiatives.…”
Section: Rural Healthcare Telemedicine and Mobile Health (Mhealth)mentioning
confidence: 99%
“…The majority of research has focused on monitoring systems which aim to detect abnormalities in patients through the integration of mobile technologies in their daily life (30,31). For instance, the pairing of a wireless heart monitor to a smartphone, and data transmission over mobile telecommunications networks would provide physicians a constant stream of reports regarding a patient's status (27,32,33). Additionally, through the use of mobile or web based applications, interaction between physician and patient can be achieved on a consistent basis regardless of distance between both parties (34,35).…”
Section: Rural Healthcare Telemedicine and Mobile Health (Mhealth)mentioning
confidence: 99%